DEM Calibration Concept for TanDEM-X - Hueso-Gonzalez, Jaime; Bachmann, Markus; Fiedler, Hauke; Huber, Sigurd; Krieger, Gerhard; Zink, Manfred (IEEE Geoscience and Remote Sensing Symposium (IGARSS), 2007)
The TanDEM-X mission [1] comprises two fully active synthetic aperture radar satellites operating in X-band. The primary goal of this mission is the derivation of a high-precision global Digital Elevation Model (DEM) according to HRTI level 3 quality [2]. This requires accurate calibration of the interferometric system parameters. Content of this paper is the development of a general concept for this calibration, which comprises the determination of instrument and baseline errors, an adjustment concept and the distribution of control points. This concept has a key incidence on mission aspects like the data acquisition plan and the data take adjustment procedure. © 2007 IEEE.
DLR Import::2019-04-03
Keywords: Calibration; Phase noise; Radar interferometry; Synthetic aperture radar